2014
DOI: 10.4236/psych.2014.511150
|View full text |Cite
|
Sign up to set email alerts
|

“Please Draw Me a Face…” Atypical Face Mental Concept in Autism

Abstract: Autism is a severe neurodevelopmental disorder characterized by early manifestations of social difficulties and atypical sensory-based behaviors. As faces are essential for social interaction, they have been widely investigated in autism, revealing disruptions in face processing. Cognitive theories argue that people with autism process the world differently, showing a processing bias for local information. However, the literature currently neglects the mental representation of faces, or face concept, in people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Two behavioral studies using emotional faces confirmed a propensity for processing local information and a deficit in global processing (Meaux et al, 2011(Meaux et al, , 2014a; however, these peculiarities were also observed for non-social stimuli (Bangel et al, 2014;Meaux et al, 2014d). We therefore suggest that while atypicalities in sensory and perceptual processing are not specific to the social domain (Clery et al, 2013c;Kovarski et al, 2017), they could strongly affect the development of social and emotional abilities in children with ASD.…”
Section: Face Processingmentioning
confidence: 63%
“…Two behavioral studies using emotional faces confirmed a propensity for processing local information and a deficit in global processing (Meaux et al, 2011(Meaux et al, , 2014a; however, these peculiarities were also observed for non-social stimuli (Bangel et al, 2014;Meaux et al, 2014d). We therefore suggest that while atypicalities in sensory and perceptual processing are not specific to the social domain (Clery et al, 2013c;Kovarski et al, 2017), they could strongly affect the development of social and emotional abilities in children with ASD.…”
Section: Face Processingmentioning
confidence: 63%